2020
DOI: 10.1536/ihj.19-270
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Plasma Adiponectin Levels Are Associated with Abnormal Corrected QT Interval in Patients with Stable Angina

Abstract: Low-circulating levels of adiponectin (ADPN) are associated with obesity, diabetes mellitus, and coronary artery disease. On the contrary, some studies have demonstrated a link between relatively high levels of plasma ADPN and heart failure, atrial fibrillation, and adverse outcome. However, little is known about the relationship between ADPN level and prolonged QT interval. The aim of this study was to investigate the association between plasma ADPN levels and prolonged QT interval in patients with stable ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
3
0
1
Order By: Relevance
“…Adiponectin and FGF21 both control the metabolism of lipids and carbohydrates, which is essential for the maintenance of energy homeostasis in the body and hence for survival. In one of our previous studies, plasma adiponectin levels have been proved to have the correlation with QTc interval prolongation [67]. A previous study further demonstrated adiponectin could mediates the metabolic effects of FGF21 [66].…”
Section: Discussionmentioning
confidence: 86%
“…Adiponectin and FGF21 both control the metabolism of lipids and carbohydrates, which is essential for the maintenance of energy homeostasis in the body and hence for survival. In one of our previous studies, plasma adiponectin levels have been proved to have the correlation with QTc interval prolongation [67]. A previous study further demonstrated adiponectin could mediates the metabolic effects of FGF21 [66].…”
Section: Discussionmentioning
confidence: 86%
“…Serum levels of the adipokine fatty-acid binding protein has also been suggested as a biochemical proxy for prolonged QTc interval and reduced ejection fraction in patients with stable angina ( 19 ). Similarly, plasma adiponectin may modulate ventricular repolarisation and thereby QTc interval ( 20 ). Given that APD prolongation manifests as QTc prolongation on 12-lead ECG, our results are compatible with adipocytokine-mediated modulation of ionic channels.…”
Section: Discussionmentioning
confidence: 99%
“…В литературе имеются данные о связи повышенного уровня адипонектина с патологическим удлинением коррегированного интервала QT на электрокардиограмме -признака электрической нестабильности миокарда [54]. В эксперименте был доказан вклад лептина в возникновение и поддержание ишемической ЖТ [55].…”
Section: биомаркеры макроокружения адипокиныunclassified